2006
DOI: 10.1021/ma060996j
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring the Global Properties of Nanocomposites. Epoxy Resins with Very Low Coefficients of Thermal Expansion

Abstract: Introduction. Cubic silsesquioxanes (see Figure 1) are unique molecules that combine three-dimensional cubic symmetry with single nanometer diameters and a core that is the smallest single crystal of silica. Symmetry places a functional group on each vertex in a different octant in Cartesian space providing the opportunity to form covalent bonds accordingly, such that the potential exists to construct materials in 1-, 2-, or 3-dimensions nanometer by nanometer. In principle, this permits manipulation of global… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
52
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 34 publications
2
52
0
Order By: Relevance
“…Sulaiman et al reported POSS composites with CTE of 20-30 mm/m/8C, made from a multifunctional epoxy resin cured by OAPS, however, OG and OC composites always showed CTE larger than 100 mm/ m/8C even it was cured by OAPS. 16 Current commercial underfills for electronic packaging are epoxy based composites with silica fillers. They exhibit low CTEs (<40 mm/m/8C is preferred) below T g .…”
Section: Thermal Expansionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sulaiman et al reported POSS composites with CTE of 20-30 mm/m/8C, made from a multifunctional epoxy resin cured by OAPS, however, OG and OC composites always showed CTE larger than 100 mm/ m/8C even it was cured by OAPS. 16 Current commercial underfills for electronic packaging are epoxy based composites with silica fillers. They exhibit low CTEs (<40 mm/m/8C is preferred) below T g .…”
Section: Thermal Expansionmentioning
confidence: 99%
“…Sulaiman et al also shows that 10% CTE drops can be reached by adding 10 wt % alumina particles in POSS composites. 16 …”
Section: Thermal Expansionmentioning
confidence: 99%
“…The cage-like inorganic core is has a size from ~ 1 nm with the structure of (SiO 1.5 ) n (n = 8, 10, or 12). [2] POSS molecules with a wide variety of surrounding organic structures have been synthesized for multifunctional applications. For underfill application, POSS have following advantages: (1) The small size of POSS mitigates the filler trapping problem between bumps and pads in capillary underfilling.…”
Section: Introductionmentioning
confidence: 99%
“…1(b) and 1(c), respectively] are frequently minor products in T 8 cube syntheses, 24)26) and their derivatives often exhibit chemical, thermal, and mechanical properties that parallel those of the T 8 derivatives. 21), 25) We have previously reported the syntheses of a variety of functionalized Q 8 SQs, including octaglycidyl SQ [OG, Fig. 2(a)] and its bifunctional (Janus) analog, [TGTSE, Fig.…”
Section: Introductionmentioning
confidence: 99%